A new species of Triplocania Roesler of the Magnifica species group (Psocodea, ‘Psocoptera’, Ptiloneuridae) from Brazil - Lima, Daniel Moura; Rafael, José Albertino; Bravo, Freddy; Silva-Neto, Alberto Moreira Da (Zootaxa, 2023)
A new species of Triplocania Roesler included in the magnifica species-group is here described, illustrated and named as: Triplocania oiapoque n. sp. based on male and female specimens. In addition to the fourth new species of the magnifica species-group, descriptions of variations in forewing venation were also made for it, as well as an additional description of the ejaculatory duct, accessory glands, and spermatic sacs, recorded for the first time in Triplocania species. A new geographic record for Triplocania magnifica Roesler and an updated species key for the magnifica species-group are also presented.